Development of microforming friction test and study of friction size-effect during microforming - Muhammad Taureza (2014)
In metal forming, lubrication and the quality of the surface finish of the tooling are carefully designed in order to control the friction. Generally, high friction in metal forming should be avoided as it results in excessive tool wear, elevated process load requirement and damaged product. However, studies have shown that due to the reduced size in microforming setup, there is a shift in friction behaviour, called the friction size-effect. Because of this shift, the knowledge of friction in metal forming such as the typical friction coefficient for certain material pairs and performance of lubricants is not applicable to microforming. Friction size-effect is therefore chosen as the core of the current studies. The investigation on friction in microforming has been conducted in the past using generic friction tests commonly known for conventional size metal forming. Realizing that fabrication and handling of micro-specimens is a difficult, time-consuming yet integral aspect in performing conventional metal forming friction test, a microforming-specific T-Shape test (or microforming T-Shape test) was developed and is presented as the key contribution of this thesis. This friction test was designed for ease of use with micro-specimens yet still offers great flexibility in allowing lubricant or certain surface finish to be evaluated. Using the modified T-Shape test, the performance of various lubricants were characterised in order to fully appraise the performance of the test and it was concluded that there is a microforming-specific phenomenon of the loss of lubricant effectiveness. In general, when a liquid or a stable liquid-based lubricant is used in microforming, its efficacy of reducing friction ceases when the contact pressure exceeds a certain value. This limit of lubricant effectiveness was further proposed as an addendum to the lubricant pocket explanation and this lubricant effectiveness limit can be used in determining the performance of lubricants. Moreover, experiments using copper have shown that the loss of lubricant effectiveness can deteriorate and as a result, lubricants may not produce friction reduction at all. In order to address this problem, tribological surface textures were considered as a non-traditional friction control solution for microforming. Past studies on surface textures have only covered their use for low pressure contact and no clear description of the friction-reducing mechanism has been given. This thesis presents the current state in the simulation work of integrating tribological surface textures to a microforming process and its effectiveness in reducing overall friction without the use of lubricant. The focus of the simulation work is given to high pressure use which is characteristic of metal forming process. Ultimately, past experimental results on indentation size effect (ISE) is also discussed in this thesis and is reconstructed into a Depth-dependent Stress-Strain relation (DSS) to explain the shift in material flow behaviour in microforming as well as to propose a simulation approach to incorporate the concept of material length scale without the numerical complexity of having gradient dependent simulation.